The Dolly case, the Polly drug, and the morality of human cloning - Schramm Fermin Roland (Escola Nacional de Saúde Pública, Fundação Oswaldo Cruz, 1999)
The year 1996 witnessed the cloning of the lamb Dolly, based on the revolutionary somatic cell nuclear transfer (SCNT) technique, developed by researchers from the Roslin Institute in Edinburgh, Scotland. This fact marked a relevant biotechnoscientific innovation, with probable significant consequences in the field of public health, since in principle it allows for expanding possibilities for the reproductive autonomy of infertile couples and carriers of diseases of mitochondrial origin. This article expounds on 1) the experiment's technical data and the theoretical implications for the biological sciences; 2) the public's perception thereof and the main international documents aimed at the legal and moral regulation of the technique; and 3) the moral arguments for and against cloning, from the point of view of consequentialist moral theory. We conclude that in the current stage of the debate on the morality of cloning, in which there are no cogent deontological arguments either for or against, weighing the probability of risks and benefits is the only reasonable way of dealing with the issue in societies that consider themselves democratic, pluralistic, and tolerant